Calotetrapterins A-C, three new pyranoxanthones and their cytotoxicity from the stem bark of Calophyllum tetrapterum Miq - Mulyadi Tanjung (Taylor & Francis, 2019)
Three new pyranoxanthones, calotetrapterins A-C (1-3) were isolated from the stem bark of Calophyllum tetrapterum Miq along with three known xanthones, a-mangostin (4), garciniafuran (5), and pyranojacareubin (6). All structures were elucidated based on their IR, UV, HRESIMS, 1 D ( 1 H, 13 C) and 2 D (HMBC, HMQC) NMR spectral data. Compounds 1-6 were tested to P-388 cells for cytotoxic activity, compound 2 exhibited high activity with IC value 1.0 lM. 50